Pengaruh Tayangan Drama Korea terhadap Pola Konsumsi Skincare dan Makeup di Kalangan Remaja - Baity, Salsabila Nur; Abdullah, Mirna Nur Alia; Rizaldi, Muhammad Retsa (Peneliti.net, 2025)
The increasing interest of Indonesian teenagers in Korean dramas has had an impact on their lifestyles, including the use of beauty products such as skincare and makeup. The purpose of this study was to find out how Korean dramas affect adolescents' preferences for using beauty products. The research method used is quantitative with a descriptive approach. The study was conducted through the distribution of an online questionnaire to adolescents aged 13 to 19 who regularly watched Korean dramas and used skincare products. The results show that the majority of teens tend to choose the beauty products shown in the drama, either directly or through their relationship with Korean artists. These results show that Korean drama shows use symbols and images of beauty to shape consumer perceptions and decisions. In conclusion, Korean dramas encourage the process of imitation and self-identity formation through the media, which has an impact on adolescent skincare and makeup consumption patterns.